1996
DOI: 10.1002/(sici)1098-108x(199605)19:4<399::aid-eat7>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant function analysis of depressive symptoms in binge eating disorder, bulimia nervosa, and major depression

Abstract: Objectives: To examine the frequency and distribution of depressive symptoms among subjects with binge eating disorder (BED), bulimia nervosa (BN), and major depression. Methods: This study examined depressive symptoms from the Hamilton Depression Scale in 122 BED, 142 BN, and 200 major depression subjects using discriminant function analysis. Results: All three groups differed significantly on the Hamilton Depression Scale totals with major depressive disorder (MDD) subjects having the highest and BED subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…For example, five to eight times as many college students meet the criteria for diagnosis of major depression and/or anxiety disorder compared to those a century ago, even when controlling for changes in diagnostic criteria and measures over the years (Twenge et al, 2010). Poor psychological well-being also is common among individuals with disturbed eating practices (Crow et al, 1996). For example, as depression and anxiety severity increase, so do disturbed eating practices, such as dietary restraint (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, five to eight times as many college students meet the criteria for diagnosis of major depression and/or anxiety disorder compared to those a century ago, even when controlling for changes in diagnostic criteria and measures over the years (Twenge et al, 2010). Poor psychological well-being also is common among individuals with disturbed eating practices (Crow et al, 1996). For example, as depression and anxiety severity increase, so do disturbed eating practices, such as dietary restraint (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that eating and affective disorders may share common aetiological and phenomenological factors, such as temperament [17], haematological status [18], genetic factors [19], biochemical irregularities [20], low self-esteem [21], cognitive styles [22], eating symptoms [16], depressive symptoms [23], attachment style [24], childhood adversity [25], and psychosocial adjustment [26]. Previous family and twin studies have shown that relatives of individuals with EDs have a greater risk for depression than relatives of controls [1, 27].…”
mentioning
confidence: 99%
“…However, all three groups showed more comorbid disorders than the patients with BED. In fact, several older studies comparing individuals with bulimia nervosa and BED have found that the former reported more comorbid psychopathology (10,11), disturbed attitudes toward weight and shape, eating pathology, depressive symptoms (11,12), dietary restraint (13), and ineffectiveness (14). The frontiers of BED with non-purging forms of bulimia nervosa, however, remains a matter of debate (15,16).…”
mentioning
confidence: 99%